Comparative haemodynamic interactions of three sole anaesthetic agents : enflurane, alfathesin and ketamine with the beta-adrenergic antagonist propranolol in the Cape chacma baboon (Papio Ursinus) during normovolaemia and acute hypovolaemia with notes on some metabolic interactions - De Roubaix, J. A. M. (Stellenbosch : Stellenbosch University, 2012)
Full text to be digitised and attached to bibliographic record.